2014
DOI: 10.1016/j.neuron.2014.06.030
|View full text |Cite
|
Sign up to set email alerts
|

ABHD6 Blockade Exerts Antiepileptic Activity in PTZ-Induced Seizures and in Spontaneous Seizures in R6/2 Mice

Abstract: The serine hydrolase α/β-hydrolase domain 6 (ABHD6) hydrolyzes the most abundant endocannabinoid (eCB) in the brain, 2-arachidonoylglycerol (2-AG), and controls its availability at cannabinoid receptors. We show that ABHD6 inhibition decreases pentylenetetrazole (PTZ)-induced generalized tonic-clonic and myoclonic seizure incidence, and severity. This effect is retained in cnr1−/− or cnr2−/− mice, but blocked by addition of a subconvulsive dose of picrotoxin, suggesting the involvement of GABAA receptors. ABHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
109
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 65 publications
1
109
1
1
Order By: Relevance
“…Therefore, the reduced production of the inflammatory prostaglandins by inhibition of ABHD6 may also contribute to the therapeutic effect of WWL70 in the EAE mouse model. Interestingly, a recent study has shown that inhibition of ABHD6 protects against pentylenetetrazole-induced seizure in C57BL/6 mice via activation of GABA A receptors, rather than activation of cannabinoid receptors (Naydenov et al, 2014). This finding is consistent with the report that 2-AG can directly activate GABA A receptor (Sigel et al, 2011), and therefore is able to maintain the balance between the inhibitory and excitatory neurotransmitters and prevent glutamate induced excitotoxicity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, the reduced production of the inflammatory prostaglandins by inhibition of ABHD6 may also contribute to the therapeutic effect of WWL70 in the EAE mouse model. Interestingly, a recent study has shown that inhibition of ABHD6 protects against pentylenetetrazole-induced seizure in C57BL/6 mice via activation of GABA A receptors, rather than activation of cannabinoid receptors (Naydenov et al, 2014). This finding is consistent with the report that 2-AG can directly activate GABA A receptor (Sigel et al, 2011), and therefore is able to maintain the balance between the inhibitory and excitatory neurotransmitters and prevent glutamate induced excitotoxicity.…”
Section: Discussionsupporting
confidence: 87%
“…Inhibition of ABHD6 has been suggested to fine-tune the 2-AG signaling in brain and shown to be effective in the animal models of traumatic brain injury and epileptic seizure (Marrs et al, 2010;Naydenov et al, 2014;Tchantchou and Zhang, 2013). Very recently, enhancement of 2-AG signaling by inhibition of its major hydrolytic enzyme MAGL is also shown to attenuate neuroinflammation and neurodegeneration in the mouse model of mild traumatic brain injury (Katz et al, 2015;Zhang et al, 2015).…”
Section: Inhibition Of Abhd6 Ameliorated Clinical Signs Of Eaementioning
confidence: 99%
“…14,27 These effects were attributed to a reduction of excitatory neurotransmission by 2-AG activation of CB1 receptors. MAGL inhibition may mediate therapeutic effects on SE by 2 main mechanisms: (1) accumulation of 2-AG, which in turn activates the neuronal presynaptic CB1 receptors, thereby reducing glutamate-mediated excitatory over inhibitory neurotransmission 28,29 or acting as allosteric modulator of c-aminobutyric acid A (GABA A ) receptors 30 ;…”
Section: Discussionmentioning
confidence: 99%
“…Chronic WWL70 treatment after traumatic brain injury exerted a neuroprotective effect by increasing the levels of 2-AG in the brain (47). Pretreating mice with WWL123, another brain-penetrant ABHD6 inhibitor, alleviated epileptic symptoms during pentylenetetrazole-induced seizures, and this blockade was absent in the presence of γ-aminobutyric acid type A receptor antagonists (48).…”
mentioning
confidence: 98%